Quantitative Evaluation of Sesame (Sesamumindicum L.) Promising Lines for Adaptability and Seed Yield in Different Agro-Climatic Conditions of Punjab (Pakistan) (Global Journal of Science Frontier Research, 2017)
Pakistan has become the fourth largest market for cooking oil after China, India and United Arab Emirates and third largest importer of the commodity. Pakistan imports crude and refined cooking oils (palm and palm olein) mainly from Malaysia and Indonesia, while it imports soybean oil from North America and Brazil. The aim of present study was to evaluate best performing sesame genotypes under different climatic conditions of Punjab province. The experiment was conducted in randomized complete block design (RCBD) with three replications at five different agro-climatic locations during Kharif 2016. Experimental material comprised of 10 genotypes with different genetic makeup. The data for seed yield was recorded and Least Significant Difference(LSD) was calculated at 5% probability level. The study showed that there is significant variability among the genotypes forseed yield. Genotypes 10003 and 50022 performed well and showed good stability in seed yield at all five locations. The cultivation of these lines in Punjab province may enhance the local production of good quality edible oil in the country.
Keywords: sesame; promising lines; agro-climate; seed yield; Punjab